Effectiveness of Omeprazole Compared to Placebo for Recurrent Abdominal Pain in Adolescents: A Randomized Controlled Clinical Trial - Yudiyanto, Ade Rachmat (Newinera Publisher, 2025)
Recurrent abdominal pain (RAP) is a common somatic complaint in adolescents, contributing to significant morbidity, impaired quality of life, and frequent school absenteeism. Although often functional in origin, proton pump inhibitors (PPIs), particularly omeprazole, are frequently prescribed under the assumption of acid-related pathology. However, clinical evidence supporting this practice in adolescents remains limited. This study aimed to evaluate the efficacy of omeprazole compared with placebo in reducing pain frequency, duration, and intensity in adolescents with RAP. A prospective, randomized, single-blind, placebo-controlled trial was conducted from August to November 2009 involving 123 adolescents aged 11–14 years who met Apley’s criteria for RAP. Participants were recruited from six junior high schools and randomized into two groups: omeprazole 20 mg once daily (n=59) or placebo (n=64), administered for 14 days. Primary outcomes included pain frequency (episodes/month), pain duration (minutes/episode), and intensity (Wong-Baker FACES Pain Scale). Assessments were performed at baseline and monthly for three months post-intervention. Results showed no significant differences between groups in pain duration or intensity (p > 0.05). Although a significant reduction in pain frequency was initially observed with omeprazole, further analysis revealed baseline imbalances, preventing attribution of this effect to the drug. Both groups demonstrated clinical improvement, reflecting a strong placebo response. In conclusion, omeprazole 20 mg daily for 14 days did not demonstrate superiority over placebo in reducing RAP frequency, duration, or intensity. These findings do not support routine empirical use of omeprazole for undifferentiated functional RAP in adolescents.